PERTOBATAN EKOLOGIS PERSPEKTIF ENSIKLIK LAUDATO SI ART. 216-218 DALAM MENANGGAPI PERSOALAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN SANGGAU - Yohanes Yovilangtus; Agustinus Agus (Lembaga Penelitian STKIP Widya Yuwana, 2023)
The focus of this study is land and forest fires in Sanggau, West Borneo from the perspective of the Encyclical Laudato Si articles 216-218. The problem that the author wants to study is human awareness in caring for, protecting and preserving the environment, as is the fact that there are humans who do not heed this. The purpose of this study is to build human awareness of the importance of preserving the environment through repentance, which is aware that environmental destruction can cause adverse effects on every living creature. The methodology used to explore this theme is a qualitative method by conducting a literature study on the concept of ecological conversion according to the Encyclical Laudato Si and other supporting book sources. This study leads the author to the finding that ignorance and careless and human being to preserve the environment is contrary to the Church's view in the Encyclical Laudato Si. Humans have a shared obligation to protect and preserve the environment. In addition, as intelligent beings, humans must have an attitude of ecological repentance, starting with an awareness of the importance of preserving and protecting the environment created by God which is a place for living things to live, grow and develop. Thus humans will be able to arrive at concrete actions, namely environmental conservation, in order to create a sense of care and awareness about the fact that they live and live with their environment.